2020
DOI: 10.1021/acs.macromol.9b01931
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Mechanical Properties, and Dynamics of Polyethylenoxide/Nanoclay Nacre-Mimetic Nanocomposites

Abstract: Nacre-mimetic nanocomposites based on high fractions of synthetic high-aspect-ratio nanoclays in combination with polymers are continuously pushing boundaries for advanced material properties, such as high barrier against oxygen, extraordinary mechanical behavior, fire shielding, and glass-like transparency. Additionally, they provide interesting model systems to study polymers under nanoconfinement due to the well-defined layered nanocomposite arrangement. Although the general behavior in terms of forming suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…Apparently, the PEG:Hec ratio applied does not perfectly meet the ratio requested for the hybrid material and consequently some Hec-only domains (Figure 3a, white arrow) are forced to segregate despite thermodynamics favouring the hybrid structure as recently suggested by Walther et al. 32 These Hec domains are, however, far thinner than the coherence length of the X-ray beam and therefore do not show up in the diffraction pattern. (ϕ= filler content).…”
Section: Resultsmentioning
confidence: 83%
“…Apparently, the PEG:Hec ratio applied does not perfectly meet the ratio requested for the hybrid material and consequently some Hec-only domains (Figure 3a, white arrow) are forced to segregate despite thermodynamics favouring the hybrid structure as recently suggested by Walther et al. 32 These Hec domains are, however, far thinner than the coherence length of the X-ray beam and therefore do not show up in the diffraction pattern. (ϕ= filler content).…”
Section: Resultsmentioning
confidence: 83%
“…Traditionally, commercial hydrophilic polymers like polyvinylalcohol (PVA), polyvinylamine (PVAm) or polyethylene oxide (PEO) were used, which however presently limits the understanding as their properties are not tailor‐made for understanding the overall mechanical behavior. [ 17,26,27 ] Detailed engineering of the polymer structure allowed to introduce new functionalities and dynamics within the internal structure of the nanocomposites through supramolecular bonds in dissociative networks. [ 21,28,29 ] Despite these advances, it is interesting to note that there are several fundamentally important issues that have not been addressed at all so far.…”
Section: Methodsmentioning
confidence: 99%
“…While there have been experimental developments toward nacre-mimetics with sequential layer-by-layer techniques and freeze-casting, one of the most facile, scalable and versatile techniques to realize artificial brick-and-mortar architectures is the colloidal self-assembly route using core/shell nanoplatelets that form lamellar phases upon drying. , Our previous work introduced this concept, and we investigated in detail how platelet size, glass transition temperature, and cross-linking influence the material properties. Other groups reported on graphene-based or MXene nacre-mimetic structures following similar evaporative self-assembly. , We also revealed that tailored dynamics of hydrogen-bonded polymers ( i.e. , dissociative dynamic covalent bonds ) can, in fact, be used to engineer sacrificial bonds and dynamic cross-links, thereby promoting combinations of stiffness and toughness beyond what covalent (nondynamic) cross-linking could offer. Moreover, light was proven to be a useful tool to break supramolecular bonds and weaken the mechanical properties of the nanocomposites through an induced photothermal effect. , …”
Section: Introductionmentioning
confidence: 99%